Blockade of PD‐1 or p38 MAP kinase signaling enhances senescent human CD8+ T‐cell proliferation by distinct pathways. Issue 5 (30th March 2015) - Henson, Sian M.; Macaulay, Richard; Riddell, Natalie E.; Nunn, Craig J.; Akbar, Arne N.
<x xml:space="preserve">Abstract</x> Immune enhancement is desirable in situations where decreased immunity results in increased morbidity. We investigated whether blocking the surface inhibitory receptor PD‐1 and/or p38 MAP kinase could enhance the proliferation of the effector memory CD8+ T‐cell subset that re‐expresses CD45RA (EMRA) and exhibits characteristics of senescence, which include decreased proliferation and telomerase activity but increased expression of the DNA damage response related protein γH2AX. Blocking of both PD‐1 and p38 MAPK signaling in these cells enhanced proliferation and the increase was additive when both pathways were inhibited simultaneously in both young and old human subjects. In contrast, telomerase activity in EMRA CD8+ T cells was only enhanced by blocking the p38 but not the PD‐1 signaling pathway, further indicating that nonoverlapping signaling pathways were involved. Although blocking p38 MAPK inhibits TNF‐α secretion in the EMRA population, this decrease was counteracted by the simultaneous inhibition of PD‐1 signaling in these cells. Therefore, end‐stage characteristics of EMRA CD8+ T cells are stringently controlled by distinct and reversible cell signaling events. In addition, the inhibition of PD‐1 and p38 signaling pathways together may enable the enhancement of proliferation of EMRA CD8+ T cells without compromising their capacity for cytokine secretion.